Neither low salivary amylase activity, cooling cooked white rice, nor single nucleotide polymorphisms in starch-digesting enzymes reduce glycemic index or starch digestibility: a randomized, crossover trial in healthy adults - Wolever, Thomas MS; El-Sohemy, Ahmed; Ezatagha, Adish; Zurbau, Andreea; Jenkins, Alexandra L (The American journal of clinical nutrition, 2021)
It was suggested that low salivary-amylase activity (SAA) and cooling or stir-frying cooked starch decreases its digestibility and glycemic index. We determined the effects of SAA, cooling, and single-nucleotide polymorphisms (SNPs) in the salivary amylase (AMY1), pancreatic amylase (AMY2A, AMY2B), maltase-glucoamylase (MGAM), and sucrase-isomaltase (SI) genes on starch digestibility and glycemic index of cooked polished rice. Healthy subjects [pilot, n = 12; main, n = 20 with low-SAA (<50 U/mL), and n = 20 with high-SAA (>105 U/mL)] consumed test meals containing 25 g (pilot) or 50 g (main) available carbohydrate at a contract research organization using open-label (pilot) or assessor-blinded (main), randomized, crossover, Latin-square designs (trial registration: NCT03667963). Pilot-trial test meals were dextrose, freshly cooked polished rice, cooked rice cooled overnight, stir-fried hot rice, or stir-fried cold rice. Main-trial test meals were dextrose, dextrose plus 10 g lactulose, plain hot rice, or plain cold rice. In both trials, blood glucose was measured fasting and at intervals over 2 h. In the main trial, breath hydrogen was measured fasting and hourly for 6 h to estimate in vivo starch digestibility. Data were analyzed by repeated-measures ANOVA for the main effects of temperature and stir-frying (pilot trial) or the main effects of SAA and temperature (main trial) and their interactions. Effects of 24 single nucleotide polymorphisms (SNPs) were assessed separately. Means were considered to be equivalent if the 95% CI of the differences were within ±20% of the comparator mean for glucose response/glycemic index or ±7% for digestibility. Pilot: neither temperature nor stir-frying significantly affected glucose incremental AUC (primary endpoint, n = 12). Main: mean ± SEM glycemic index (primary endpoint, n = 40) was equivalent for low-SAA compared with high-SAA (73 ± 3 vs. 75 ± 4) and cold rice compared with hot rice (75 ± 3 vs. 70 ± 3). Estimated starch digestibility (n = 39) was equivalent for low-SAA compared with high-SAA (95% ± 1% vs. 92% ± 1%) and hot rice compared with cold rice (94% ± 1% vs. 93% ± 1%). No meaningful associations were observed between genotypes and starch digestibility or glycemic index for any of the SNPs. The results do not support the hypotheses that low-SAA, cooling, and common genetic variations in starch-digesting enzymes affect the glycemic index or in vivo carbohydrate digestibility of cooked polished rice. This trial was registered at clinicaltrials.gov as NCT03667963.